Assessment of the Business Proposals Using Frank Aggregation Operators Based on Interval-Valued T-Spherical Fuzzy Information. (8th April 2022) - Hussain, Amir; Ullah, Kifayat; Wang, Haolun; Bari, Mehwish
Abstract : An interval-valued T-spherical fuzzy set (IVTSFS) is an efficient framework to treat ambiguous and vague information more efficiently. It has four functions consisting of the information in intervals. With the help of these functions, IVTSFS is a more reliable framework than the other existing frameworks. This article aims to establish algebraic operations of IVTSFSs named Frank sum, Frank multiplication, and Frank scalar multiplication stranded on Frank t-norm and t-conorm. Further, some averaging and geometric aggregation operators (AOs), i.e., interval-valued T-spherical fuzzy Frank weighted averaging (IVTSFFWA) and interval-valued T-spherical fuzzy Frank weighted geometric (IVTSFFWG) operators are established based on the defined operations, and then the properties of these operators are observed. The proposed approach is supported by an illustrative example, in which we have applied our proposed approach to a multiattribute group decision-making (MAGDM) problem. For the significance of the proposed approach, a comparative study is done. The various effects of the variation of parameters are also investigated which plays an important role in the final results.